2017
DOI: 10.1111/jftr.12202
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Family Leisure and Family Quality of Life: A Meta‐Analysis of Data from Parents and Adolescents

Abstract: The body of family leisure research has grown over the past 25 years; however, efforts to quantitatively synthesize that body of literature have not been made. Therefore, we conducted a meta‐analysis of published and unpublished literature reporting on parent and adolescent child data regarding shared leisure experiences and family quality‐of‐life indicators across k = 23 articles identified from a broad, systematic search of literature. Using random effects, we measured the associations of (a) family leisure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 65 publications
0
27
0
11
Order By: Relevance
“…Leisure time with children, heretofore considered contaminated by several important studies, was in fact typically experienced more positively than pure leisure. When possible, future research should use direct measures of how individuals experience their leisure time to better understand how the context of families and time shapes well‐being (Hodge et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Leisure time with children, heretofore considered contaminated by several important studies, was in fact typically experienced more positively than pure leisure. When possible, future research should use direct measures of how individuals experience their leisure time to better understand how the context of families and time shapes well‐being (Hodge et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For decades, family and leisure scholars have suggested that couples should spend their time together in rituals, routines, and recreation to provide predictable, regular interactions that enhance couples' relationships (e.g., Doherty, ; Fiese, ; Orthner, ; Schwab & Dustin, ; Zabriskie & McCormick, ). Scholars from these fields describe the positive association between family leisure activities and family bonding (Fiese, ; Hodge et al, , Orthner & Mancini, 1990; Townsend, Van Puymbroeck, & Zabriskie, ; Zabriskie & McCormick, ); yet no studies from these fields have examined the underlying mechanisms of family leisure activities that produce family bonding.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In relations to family well‐being, previous literature has identified a significant difference between core‐ and balance‐forms of leisure related to family functioning, cohesion, adaptability, and satisfaction with family life (e.g., Townsend et al, ; Zabriskie & McCormick, ). Overall, findings suggest that core (i.e., familiar) and balance (i.e., novel) family leisure promote family functioning; specifically, core family leisure is a stronger and more consistent predictor of family quality of life (Hodge et al, ; Melton & Zabriskie, ; Townsend et al, ). Other literature has noted the differences between parallel‐ and joint‐forms of leisure in marital satisfaction (e.g., Orthner, ; Holman & Epperson, 1984).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfying family leisure experiences are a key conduit for developing individual and family resilience. Leisure facilitates stress recovery (Lazarus, Kanner, & Folkman, ) and contributes to aspects of subjective well‐being such as improved quality of life (Brajša‐Žganec, Merkaš, & Šverko, ) and improved quality of family life (Hodge et al, ). Specifically, research from the past 20 years examining patterns of family leisure has identified that satisfaction with family activities is a stronger predictor of quality of family life than is amount of time spent in family activities (see Hodge et al, ).…”
mentioning
confidence: 99%